2014
DOI: 10.4103/0973-1296.126656
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography determination and pharmacokinetics of coumarin compounds after oral administration of Samul-Tang to rats

Abstract: Background:Samul-tang has been traditionally used for the treatment of cardiovascular, gynecologic, cutaneous, and chronic inflammation disorders. Although coumarin compounds do have various pharmacological activities and the same may be present in Samul-tang, however there is little information about it.Objective:A simple and sensitive high-performance liquid chromatography (HPLC) method has been developed for the determination of nodakenin, nodakenetin, decursin, decursinol, and decursinol angelate in rat pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…33 Al-Amiery et al have synthesized 4-[(5-mercapto-4-phenyl-4H-1,2,4triazol-3-yl)-methoxy]-2H-chromen-2-one as coumarin derivatives and their antifungal activity was determined based on the growth inhibition rates of the mycelia of strains of Aspergillus niger and Candida albicans in Potato Dextrose Broth medium (PDB) against concentrations ranging from 10 to 100µgml -1 . Two compounds (5,6) showed good activity as antifungals against fluconazole standard drug. 34 Behrami et al synthesized 8-amino-4,7-dihydroxy-chromen-2-one coumarin derivatives.…”
Section: Antimicrobal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…33 Al-Amiery et al have synthesized 4-[(5-mercapto-4-phenyl-4H-1,2,4triazol-3-yl)-methoxy]-2H-chromen-2-one as coumarin derivatives and their antifungal activity was determined based on the growth inhibition rates of the mycelia of strains of Aspergillus niger and Candida albicans in Potato Dextrose Broth medium (PDB) against concentrations ranging from 10 to 100µgml -1 . Two compounds (5,6) showed good activity as antifungals against fluconazole standard drug. 34 Behrami et al synthesized 8-amino-4,7-dihydroxy-chromen-2-one coumarin derivatives.…”
Section: Antimicrobal Activitymentioning
confidence: 99%
“…There are a number of reports that natural and synthetic Coumarin derivatives posses antimicrobial activity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Novobiocin and Chlorobiocin are established antimicrobials containing a Coumarin (i.e.2H-1-benzopyran-2-ones) skeleton, there are many Coumarin derivatives which have been reported for anticoagulant, anti-inflammatory, anti-HIV, antioxidant, anti-allergic, anti-cancer, anti proliferative and antiviral activities. [15][16][17] It was found that when one biodynamic heterocyclic system was coupled with another heterocyclic system, enhanced biological activity was produced.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these pharmacological activities, pharmacokinetic (PK) studies for major components of AGN are limited. Several PK studies of AGN in mice [ 13 ], rats [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and humans [ 23 ] have been published. Most of them have characterized PKs of one or two components of courmarins from extracted AGN or shown PKs of combined D and DA.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them have characterized PKs of one or two components of courmarins from extracted AGN or shown PKs of combined D and DA. One publication has reported PKs for four coumarins of D, DA, nodakenin, and DOH [ 14 ]. However, only combined D and DA could be evaluated in that study because their analytical methods could not separate isomeric peaks of D and DA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation